Skull anatomy of Wilson’s storm-petrel Oceanites oceanicus (Hydrobatidae, Procellariiformes) - Piro, Alejandra; Acosta Hospitaleche, Carolina Ileana Alicia (Polar Biology)
Oceanites oceanicus (Procellariiformes, Hydrobatidae), commonly known as Wilson’s storm-petrel, is a small seabird frequenting the South Atlantic Ocean during the austral summer. Although a number of adaptations (such as the development of salt glands, two long and tubular external nostrils, an extraordinary olfactory system, and a hooked bill covered by several horny plates) are shared with all other Procellariiformes, the ongoing discrepancy between molecular and morphological data highlights the limited osteological information available for O. oceanicus. However, we strongly believe that osteology provides significant information to understand the evolutionary history of different groups of birds. Comparative analysis of the cranium and mandible shows that adult specimens of O. oceanicus have a globose and completely fused cranium without visible sutures, and a short beak. Besides, as in other storm-petrels, the fossa glandulae nasale is interrupted by the development of the processus postocularis and the angulus postocularis; the os lacrimale develops a complex structure, with a fenestra innominata between the rostral process of the lacrimal and the os frontale; the lamina parasphenoidalis has a simpler structure with poorly defined boundaries and without processi; and the processi basipterigoidea are present. Fil: Piro, Alejandra. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico Zoología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina